Penerapan Media Pembelajaran Audio Vidio Sistem Rem Cakram Untuk Meningkatkan Minat Belajar Siswa - Dwi Jatmoko; Arif Susanto; Mike Elly Anitasari; Ahmad Ainul Yaqin; Widiyatmoko Widiyatmoko (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This research aims to find out how the application of audio video learning media for disc brake systems can increase students' interest in learning about the subject of disc brake systems in class XI TSM SMK Ma'arif NU 1 Bener. To find out how interested students are in learning after implementing audio video learning media for motorbike disc brake systems. The research method used is classroom action research. The results of this research in cycle I show that there is still a lack of student interest in learning, this is shown by the results of distributing questionnaires conducted by researchers which show the score in cycle I is 2262 with a percentage of 70% and in cycle I there is an increase, namely getting a total score of 2399 with a percentage of 80 %.